A 1.2-V 0.959-ppm/°C multi-section curvature-compensated bandgap voltage reference with trimming. (June 2023) - Chen, Qibin; Gong, Yihong; Tu, Ruiyong; Xie, Jin; Dai, Haiyan; Chen, Yinrong; Wei, Rongshan; Li, Jinghu; Luo, Zhicong
Abstract: This article introduces a high-precision and low temperature coefficient(TC) bandgap reference (BGR) with a 1.2 V output voltage after a novel digital trimming. A multi-section curvature compensation circuit alleviates the variation caused by the temperature dependence of the base emitter nonlinear voltage of bipolar transistors. The novel digital trimming technology is utilized to reduce the TC and improve the output voltage precision(VP) of the proposed the BGR. Designed and simulated in a 65 nm CMOS process with an active area of 0.037 mm 2 . Simulation results of the proposed the BGR demonstrates that its output voltage is 1.2 V, the best TC is 0.959 ppm/°C over a −40 °C to 125 °C temperature range and the power consumption of 138 μ W under 3.3 V supply voltage at room temperature with trimming. In the supply voltage range of 1.8–3.4 V, the line regulation (LR) is 0.25%/V.